(untitled) (Journal of Economic Research & Business Administration, 2016)
In conditions of intensified competition, the role of innovative projects, and accordingly, the quality of their management. The traditional approach of management based on detailed planning and carefully designed processes, in the field of innovative projects can no longer be considered sufficiently effective and acceptable. Therefore careful consideration of the specific nature of innovative projects and their accounting in the management process.